La civilisation économique : interdisciplinarité exemplaire ou limite de l’interdisciplinarité ? - Vanessa Boullet (Revue Française de Civilisation Britannique)
This paper will analyse the notion of interdisciplinary research and teaching through the lens of economic civilisation. Civilisation research covers the various dimensions of cultural, social or historical events. It refers to and uses a number of disciplines and methods borrowed notably from humanities and social sciences. Civilisation is essentially interdisciplinary and cannot be adequately comprehended using only one discipline (such as sociology, history or economics). This might explain why the image of civilisation is sometimes tarnished by a lack of scientific recognition or why non-French lecturers and researchers are often puzzled by lectures in “civilisation”. Adding the word ‘economics’ to form ‘economic civilization’ does not make it any easier.How can we define this research area that in essence goes beyond the frontiers of disciplines to create meaning? Is this research pluri-disciplinary in nature, leveraging several fields of studies without combining them? Is it interdisciplinary as, it uses the methods of one or several of the disciplines to enhance another discipline? Or, is it transdisciplinary, going beyond the disciplinary debate to the point of sometimes creating a whole new field of study to shed new light on old questions, but taking the risk of creating a muddled assemblage of ideas without solid foundations?